Stand structure of tropical forests is strongly associated with primary productivity - Wenmin Zhang; Yanbiao Xi; Martin Brandt; Chunying Ren; Jialing Bai; Qin Ma; Rasmus Fensholt (Communications Earth & Environment)
Abstract Stand structure influences the distribution of light and water and thus affects the functioning of forest ecosystems. However, information on stand structure capturing both horizontal and vertical structures of forest canopies simultaneously is lacking. Here we use principal component analysis to derive a stand structural indicator (SSI) index based on four structural metrics derived from GEDI covering tropical forests and upscale the GEDI footprint-level SSI to a spatially continuous distribution using Sentinel-1&2 imagery. The majority of high SSI values representing higher forest height, density and diversity of canopy height, is found for all tropical forest areas in moist regions, natural forests, and regions with less fire activity. We show that SSI is positively correlated with primary productivity and that the sensitivity of productivity to SSI is larger in natural forests than in managed forests. Our results highlight synthesized stand structure information to support sustainable forest management and conservation.